The Impact of Communication Between Teachers and Students: A Case Study of the Faculty of Management Sciences, University of Karachi, Pakistan - Zaeema Asrar; Noman Tariq; Hira Rashid (European Scientific Journal, ESJ, 2018)
Student’s relationship with teachers is important because students spend about 7 to 9 hours a day and almost 11 months with the teacher. This paper focuses on ascertaining the impact of communication between teachers and students. Communication is a motivational tool for students to accomplish their studies. In this era, education is spreading very quickly all around the world. Universities are trying to improve their standard by increasing the quality of education as well as the quality of their students. This study examines the challenges which create barriers and huddles due to communication between the teachers and students to ensure that the students succeed. For this purpose, the faculty of management science, University of Karachi, Pakistan, was used as a case study. Its impact on students through the teacher’s communication was examined. Three (3) departments are working under the faculty of management science. The random sampling method was used to gather the data from the departments. Descriptive analysis of mean and percentage were applied to find the impact of teacher’s communication on the student’s education and their success. The results show a positive relation between them. It is very difficult to create a positive relation between teachers and students when they get to a certain stage. This is because they are both mature, although it is necessary for both students and teachers. The qualities for a positive relationship can vary to make learning experience approachable and inviting for the students. If the teacher and the students have good communication skills and understand the importance of the impact of their communication, establishing a good relationship will be much easier. This research paper, however, shows that there is a positive relation between teachers and students which creates goodwill for the teachers and makes the students to be result-oriented.